Kompang illustration by using equation of curve - Ramli, Masnira; Che Mat, Rosfatihah; Rejab, Zati Ascha; Saridon, Nalle Nor Lyana; Mukmin, Mohd Asmirul Fikri (Universiti Teknologi MARA, Kedah, 2023)
Mathematics, culture, and arts are mutually influential where the relation of mathematics in culture and arts already exists from the past. The expansion of knowledge on ethnomathematics leads to the relationship between mathematics and culture. In Malaysia, there are many cultures, which the main are Malay culture, Indian culture, Chinese culture, etc. However, this study will focus on Malay culture and its musical instrument, the kompang. Kompang is the Malay community’s common traditional musical instrument. Culture involves the shared understandings through which individuals interact with each other, but to see it from a mathematical perspective, some study needs to be carried out, like how the equations can illustrate the image of kompang. To see the physical features of kompang through mathematics, the equation of kompang will be produced by using the equation of a circle and the equation of a quadratic bezier curve. The formulation of the equation for kompang is made using Maple software. Through observation and measurement of actual kompang, the information is used to form the image of kompang and the equation of kompang. From the result, we can see how mathematics can relate to culture and vice versa, and it gives another idea in the classroom to see the application of mathematics from another perspective. Whatever is around us has its own mathematical point of view, and through this study, we believe the flexibility of the equation can form a variety of shapes like kompang.